Environmental regulation and investment: Evidence from European country-industry data - Andrea M. Leiter; Arno Parolini; Hannes Winner (University of Salzburg, Department of Social Sciences and Economics, 2010)
This paper contributes to the empirical literature on the relationship between environmental regulation and firm behavior. In particular, we ask whether and how strongly an industry's investment responds to stringency in environmental regulation. Environmental stringency is measured as (i) an industry's total current expenditure on environmental protection, and (ii) a country's revenue from environmental taxes. Focusing on European industry level data between 1995 and 2005, we estimate the differential impact of environmental stringency on four types of investment: gross investment in tangible goods, in new buildings, in machinery, and in `productive' investment (investment in tangible goods minus investment in abatement technologies). Both environmental variables enter positively, and their quadratic terms exhibit significantly negative parameter estimates. This, in turn, indicates a positive but diminishing impact of environmental regulation on investment.
Keywords: D92; H23; Q52; 330; Investment; environmental regulation; pollution abatement costs; Europe